Longitudinal effect of HCV cure on markers of kidney disease - Javier Cepeda; Mohamed Atta; Katie Zook; Miles Landry; Paula Maier; George Schwartz; Gregory Lucas (PLoS ONE, 2025)
Chronic hepatitis C infection has been linked to chronic kidney disease. Despite availability of all oral highly curative direct acting antiviral treatment for more than a decade, impact of HCV cure on extrinsically measured iohexol glomerular filtration rate (iGFR), a marker of kidney function, has not been rigorously evaluated. Over two recruitment periods (October 14, 2010 – July 23, 2012 and December 15, 2015 – September 12, 2019), we enrolled 208 participants with chronic HCV infection, 63% of whom were co-infected with HIV. We conducted linear mixed effects modeling to evaluate the change in iGFR slope among participants who were and were not cured from chronic HCV. Secondary outcomes included albuminuria (urine albumin-creatinine-ratio ≥30 mg/g). At baseline, the median age was 51 years (interquartile range: 47–56), most of whom were Black (85%), and male (71%). In the multivariable-adjusted model, including baseline iGFR and other covariates, the adjust difference in iGFR slope was 2.37 mL/min/1.73 m2 per year (95% CI: 0.72, 4.03, p = 0.0051) higher among HCV treated participants compared to untreated. HCV treatment status was not associated with probability of albuminuria. Among participants chronically infected with HCV, we identified a significant positive impact of HCV cure on kidney function over time. While iGFR declined overall, declines were attenuated among participants treated for HCV compared to participants who remained untreated.